A structural common factor approach to core inflation estimation and forecasting - Claudio Morana (European Central Bank (ECB), 2004)
In the paper we propose a new methodological approach to core inflation estimation, based on a frequency domain principal components estimator, suited to estimate systems of fractionally cointegrated processes. The proposed core inflation measure is the scaled common persistent factor in inflation and excess nominal money growth and bears the interpretation of monetary inflation. The proposed measure is characterised by all the properties that an “ideal” core inflation process should show, providing also a superior forecasting performance relative to other available measures.
Keywords: C22; E31; E52; 330; common factors; core inflation; euro area; fractional cointegration; long memory; Markov switching